1995
DOI: 10.1210/jcem.80.4.7714094
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of plasma adrenocorticotropin and cortisol levels in critically ill patients: possible role of endothelin and atrial natriuretic hormone.

Abstract: The regulatory mechanisms of the hypothalamo-pituitary-adrenal system were studied in critically ill, intensive care unit patients. Serial measurements of immunoreactive ACTH-(1-39) (ACTHi), cortisol, endothelin-1 (ETi), and atrial natriuretic hormone (ANHi) were performed in blood samples of 18 patients with clinically defined sepsis, 12 critically ill patients after multiple trauma, and 15 hospitalized matched control subjects without acute illness for 8 consecutive days after admission. On admission, plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 24 publications
2
75
1
5
Order By: Relevance
“…Interestingly, in 30 patients, unstimulated plasma cortisol values were above 0.55 ~mol/1 while plasma ACTH was within the reference value (20-80ng/1). Although the pulsatile character of ACTH secretion limits the interpretation of a single ACTH measurement in the individual patient, the lack of correlation between ACTH and cortisol levels -a finding previously reported [12,13] -and reports of a hiphasic action response of the hypothalamic-pituitaryadrenocortical (HPA) axis in critically ill patients [14] and in patients undergoing abdominal surgery [15], showing high cortisol and ACTH levels in the first 2-4 clays with a subsequent sharp decrease in ACTH while cortisol levels remained high, provide further evidence that HPA activation during a critical illness is a complex process in which mechanisms other than simple feedback between ACTH and cortisol play a role. In this group of 54 patients with RAAA, one patient with an APACHE II score of 14 did not meet the criteria for normal adrenocortical function; the plasma cortisol value after ACTH stimulation was was 0.47 btmol/1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in 30 patients, unstimulated plasma cortisol values were above 0.55 ~mol/1 while plasma ACTH was within the reference value (20-80ng/1). Although the pulsatile character of ACTH secretion limits the interpretation of a single ACTH measurement in the individual patient, the lack of correlation between ACTH and cortisol levels -a finding previously reported [12,13] -and reports of a hiphasic action response of the hypothalamic-pituitaryadrenocortical (HPA) axis in critically ill patients [14] and in patients undergoing abdominal surgery [15], showing high cortisol and ACTH levels in the first 2-4 clays with a subsequent sharp decrease in ACTH while cortisol levels remained high, provide further evidence that HPA activation during a critical illness is a complex process in which mechanisms other than simple feedback between ACTH and cortisol play a role. In this group of 54 patients with RAAA, one patient with an APACHE II score of 14 did not meet the criteria for normal adrenocortical function; the plasma cortisol value after ACTH stimulation was was 0.47 btmol/1.…”
Section: Discussionmentioning
confidence: 99%
“…This biphasic response has been observed among adults with sepsis and adults with severe multiple trauma [41]. In addition to the components of the HPA axis, cytokines and other immune mediators play roles in the response to acute stress.…”
Section: Hpa Axis and Stress: Clinical And Animal Studiesmentioning
confidence: 96%
“…However, an observation which does not support such an HPA-axis activation during critical illness is the low plasma ACTH. Vermes et al (40) showed that plasma ACTH concentrations in patients suffering from severe trauma or sepsis were only transiently elevated and after a few days dropped below those observed in healthy control subjects in the face of high plasma cortisol. Furthermore, in a more heterogeneous long-stay ICU patient population, plasma ACTH concentrations were found to be suppressed from day 1 in ICU throughout the first week of critical illness, again in the presence of high plasma cortisol (41).…”
Section: Rai In Critical Illnessmentioning
confidence: 99%
“…First, if a primary adrenal failure would be the reason for an insufficiently increased cortisol production and thus insufficiently increased plasma cortisol concentrations, one would expect a high plasma ACTH concentration, which has not been reported (40,41). Secondly, it was shown that the cortisol incremental cortisol response to an ACTH stimulation test in critically ill patients correlated positively with both cortisol production rate and cortisol plasma clearance (41) (Fig.…”
Section: E Boonen and G Van Den Berghementioning
confidence: 99%